2015
DOI: 10.19082/1542
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pap Smear and Colposcopy in Screening for Cervical Cancer in Patients with Secondary Immunodeficiency

Abstract: IntroductionCervical cancer is the second most common cancer among women worldwide. The sensitivity of conventional Pap smear in detecting cervical lesions before cervical cancer is 51%, which means the false negative value is 49%. The aim of this study was to compare two methods for screening for cervical cancer in patients with secondary immunodeficiency, i.e., the conventional Pap smear and colposcopy.MethodsThis cross-sectional study was conducted on 101 immunodeficient patients who were referred to the Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
2
13
1
Order By: Relevance
“…In this study we evaluated how PAP Smear test, VIA and VILI could be used as screening methods in Nord west of Cameroon. The gold standard test for cervical cancer screening is indeed colposcopy, it has been used to demonstrated limit of the PAP Smear in terms of accuracy, sensitivity, specificity, and negative predictive values in detecting highgrade, cervical, pre-malignant lesions [18]. But in the context of our study, we were unable to get access to this test.…”
Section: Discussionmentioning
confidence: 76%
“…In this study we evaluated how PAP Smear test, VIA and VILI could be used as screening methods in Nord west of Cameroon. The gold standard test for cervical cancer screening is indeed colposcopy, it has been used to demonstrated limit of the PAP Smear in terms of accuracy, sensitivity, specificity, and negative predictive values in detecting highgrade, cervical, pre-malignant lesions [18]. But in the context of our study, we were unable to get access to this test.…”
Section: Discussionmentioning
confidence: 76%
“…[11] Mojgan et al (2015) observed that 20.3% of HIV patients had abnormal Pap smears and 10.7% of them had abnormal colposcopy. [12] It was observed that the maximum incidence of epithelial abnormalities was between the age group of 31-40 years. Both the patients with squamous cell carcinoma were under the age of 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Though conventional PAP smear was used in this study, various studies have demonstrated significant relationship between conventional PAP smear, Liquid based cytology (LBC) and Colposcopy method. Karimi-zarchi et al has compared the results of conventional PAP smear, Liquid based cytology and Colposcopy method and found that Colposcopy with sensitivity of 70.9% can be stated to be superior than LBC PAP with sensitivity of 55.3% and in the comparison of compliance of the conventional PAP smear with that of the LBC, no significant relationship was found [ 13 ]. Thus, general colposcopy method has a higher sensitivity in diagnosis of any cervical lesions compared to the conventional PAP smear and liquid-based PAP smear.…”
Section: Discussionmentioning
confidence: 99%